2009
DOI: 10.1085/jgp.200910273
|View full text |Cite
|
Sign up to set email alerts
|

Flux regulation of cardiac ryanodine receptor channels

Abstract: The cardiac type 2 ryanodine receptor (RYR2) is activated by Ca2+-induced Ca2+ release (CICR). The inherent positive feedback of CICR is well controlled in cells, but the nature of this control is debated. Here, we explore how the Ca2+ flux (lumen-to-cytosol) carried by an open RYR2 channel influences its own cytosolic Ca2+ regulatory sites as well as those on a neighboring channel. Both flux-dependent activation and inhibition of single channels were detected when there were super-physiological Ca2+ fluxes (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 40 publications
1
54
2
Order By: Relevance
“…The RyR2 channel is likely to be modulated by SR Ca 2+ load via some luminal Ca 2+ sensing mechanisms [28-32]. CASQ2 is commonly believed to act as the luminal Ca 2+ sensor responsible for the regulation of Ca 2+ release by SR luminal Ca 2+ [29,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RyR2 channel is likely to be modulated by SR Ca 2+ load via some luminal Ca 2+ sensing mechanisms [28-32]. CASQ2 is commonly believed to act as the luminal Ca 2+ sensor responsible for the regulation of Ca 2+ release by SR luminal Ca 2+ [29,33].…”
Section: Discussionmentioning
confidence: 99%
“…How elevating SR Ca 2+ load opens the RyR2 channel and triggers SCWs is unclear. The RyR2 channel is thought to be regulated by an intra-SR Ca 2+ sensing mechanism(s) that promotes RyR2 opening as SR Ca 2+ content rises [28-32]. The molecular nature of the intra-SR Ca 2+ sensor is debated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of chimerical channels of mammalian Slo1 and dSlo1 revealed that the S0 TM segment is important for the functional effects of β subunits (Wallner et al, 1996; Morrow et al, 2006; Lee et al, 2010). By engineering disulfide linkages, Marx and colleagues model S0 outside of the VSD adjacent to the S3 and S4 helices, while the two TM segments of the β subunits (TM1 and TM2) are packed close to each other at the mouth of the cleft between VSDs of two adjacent Slo1 subunits (Liu et al, 2008a, 2010; Figure 1B). Within this cleft, TM1 is close to S1 of one VSD and TM2 close to S0 of the adjacent VSD (Liu et al, 2008b, 2010; Wu et al, 2009; Zakharov et al, 2009).…”
Section: Bk Channel β Subunitsmentioning
confidence: 99%
“…One proposed mechanism, the “feed-through” hypothesis, suggests that luminal Ca 2+ passes through an open RyR2 and acts on its own cytosolic Ca 2+ activation site 14, 36 . However, there is an accumulating body of evidence indicating that luminal Ca 2+ activation of single RyR2 is mediated by some luminal Ca 2+ sensing mechanism(s) that is (or are) structurally distinct from the RyR’s cytosolic Ca 2+ activation site 13, 19, 3740 . The molecular nature of the luminal Ca 2+ sensing mechanism(s) is poorly understood.…”
Section: Introductionmentioning
confidence: 99%